STRATEGI MUSEUM BATIK PEKALONGAN TERHADAP PENINGKATAN MINAT EDUPRENEURSHIP DAN BUDAYA BATIK BAGI GEN Z - Muhammad Zakki Musyafa; Septia Rosada; Neza Dwi Nasyfa; Ferida Rahmawati (CV. Denasya Smart Publisher, 2025)
This study examines how the Pekalongan Batik Museum fosters interest in edupreneurship and strengthens batik culture among Generation Z. The study used a descriptive qualitative approach, using in-depth interviews and direct observation. The results indicate that the museum implements experiential learning strategies, such as batik workshops, assistance in designing batik motifs, and collaboration with MSMEs and local batik communities. This strategy not only enhances understanding of batik culture but also helps develop creative skills and awareness of batik's economic value as a business opportunity. However, several obstacles remain, including the lack of use of digital technology and low local community participation. These findings suggest that the experiential edupreneurship model developed by the Pekalongan Batik Museum can be replicated by other batik museums and similar cultural institutions to support cultural preservation and foster a creative economy ecosystem among the younger generation..